Severe Case of Autoimmune Thrombocytopenia First Diagnosed in Pregnancy - Bolten, K.; Salama, A.; Thomas, A.; Eucker, J.; Henrich, W. (Geburtshilfe und Frauenheilkunde, 2013)
We report on a 28-year old primigravida who presented in the second trimester with sudden onset of bleeding tendencies and thrombocytopenia of 2/nL during the first manifestation of autoimmune thrombocytopenia (ITP). Therapy with intravenous immunoglobulins (IVIG) and steroids was initiated but could not prevent renewed bleeding incidents and recurrent thrombocytopenia in the long term, thus premature delivery by Caesarean section in the 32 + 3 week of pregnancy could not be avoided. The bleeding complications could only be mastered by multiple thrombocyte transfusions. Because the ITP remained refractory to therapy in the postpartum period a thrombopoietin receptor agonist (TPO-RA) was administered. This led to an increase in the thrombocyte count which was later stabilised by prednisolone alone.
Keywords: pregnancy; ITP; autoimmune thrombocytopenia; obstetrics; premature birth; coagulopathy